Social citizenship for whom? young Turks in Germany and Mexican Americans in the United States - Faist, Thomas 1959- (Avebury, 1995)
Auth: University of Bremen, Finds that under both systems immigrants do badly.
Keywords: Burgerschap; Immigranten; Mexicanen; Sociale grondrechten; Turken; Children of foreign workers -- Germany -- Social conditions; Mexican American children -- Social conditions; Mexican Americans -- Social conditions; Turks -- Germany -- Social conditions; Ausländischer Jugendlicher; Integration; Türkischer Jugendlicher; Chicanos; Soziale Integration; Mexikanischer Jugendlicher; Soziale Situation; Jugend; Deutschland; USA; Germany -- Ethnic relations; United States -- Ethnic relations